DNA damage repair gene germline profiling for metastatic prostate cancer patients of different ancestries. Issue 12 (2nd June 2022) - Abdi, Bilal; Basset, Noemie; Perrot, Emmanuel; Benderra, Marc‐Antoine; Khalil, Ahmed; Oudard, Stephane; Blanchet, Pascal; Brureau, Laurent; Coulet, Florence; Cussenot, Olivier; Cancel‐Tassin, Geraldine
Abstract: Background: Germline and somatic mutations in DNA damage repair genes (DDRg) are now recognized as new biomarkers for the management of metastatic prostate cancers (mPC). We evaluate the frequency of germline DDRg mutations among French mPC patients of European and African ancestries. Methods: Targeted next‐generation sequencing of 21 DDRg was performed on germline DNA from 557 mPC patients, including 15.1% of cases with an African origin. Results: Forty‐seven germline mutations in 11 DDR genes were identified in 46 patients of the total cohort (8.3%). BRCA2 (4.1%) and ATM (2.0%) were the most frequently mutated genes. There was no difference in DDRg mutation frequency between mPC patients of European ancestry and those of African origin. Germline mutations of BRCA2 were associated with a positive family history of breast cancer ( p = 0.02). The mean age at metastatic stage (59.7 vs. 67.0; p = 0.0003) and the mean age at death (65.2 vs. 73.9; p = 0.0003) were significantly earlier for carriers of BRCA2 mutation than for non‐carriers. Moreover, the Cox model showed that BRCA2 positive status was statistically associated with poorer survival (hazard ratio: 0.29; 95% confidence interval 0.18–0.48; p < 0.0001). Conclusion: We showed that, in France, BRCA2 and ATM are the main predisposing DDR genes in mPC patients, with a particular aggressiveness for BRCA2 leading to early metastatic stage and death.